The Relationship Between Age, Education, Region, and Knowledge with Stunting Prevention Attitudes in Brides-to-Beat the Religious Affairs Office (KUA) - Quraisy, Cut Cahaya Rani Saifa Alhajd; Probandari, Ari Natalia; Widyaningsih, Vitri (Nusantara Science and Technology Proceedings, 2024)
The high prevalence of stunting in West Aceh Regency can be caused by low public awareness to prevent stunting early on through various activities or programs to improve community attitudes, especially in prospective brides as a determining factor that contributes to the problem of stunting due to the age of marriage too early, the low education of prospective brides who are in rural areas, and the lack of information about the importance of stunting prevention by prospective brides. The purpose of this study was to determine the relationship between age, education, region, and knowledge with attitudes to prevent stunting in prospective brides. This research was conducted at the Religious Affairs Office (KUA) of West Aceh Regency, namely the KUA of Meureubo, Kaway XVI, Johan Pahlawan, and Samatiga Districts. This study used a cross-sectional design. The research sample was prospective brides who were selected proportionally according to each location using purposive techniques based on the results of sample calculations on unknown populations according to the Lemeshow formula with the acquisition of 108 respondents. Data collection used a questionnaire that had been validated using validity and reliability tests for the variables of knowledge and attitudes to prevent stunting. The data that has been collected is analyzed using the chi-square test to conclude the problem under study. The results of statistical analysis showed that age and education, both of which had a P.Value smaller than the alpha probability of 0.05, showed that age and education were not associated with stunting prevention attitudes in prospective brides. Meanwhile, region and knowledge obtained a P.Value value greater than the probability alpha 0.05, indicating that region and knowledge are significantly related to the attitude of stunting prevention in prospective brides at the KUA of West Aceh Regency.